In vitro differentiation of common lymphoid progenitor cells into B cell using stromal cell free culture system - Pan Yang; Xiaoling Chen; Hao Wen; Meiling Yu; Haili Yu; Li Wang; Liang Gong; Lintao Zhao (BMC Immunology)
Abstract The OP9 culture system is an important in vitro model for B cell development. However, the complex nature of operations and the intrinsic variability of stromal cell functionality, which can be influenced by factors such as radiation exposure or contamination, pose considerable challenges to their wider application. Currently, there exists a paucity of studies documenting in vitro B cell differentiation culture systems that exclude stromal cells, and the experimental methodologies available for reference remain limited. This report elucidates a robust stromal cell-free culture system. Specifically, bovine serum albumin (BSA) or fetal bovine serum (FBS), in conjunction with interleukin-7 (IL-7), Flt3 ligand (Flt3L), and stem cell factor (SCF), were incorporated into X-VIVO15 medium. This system proficiently facilitates the directed differentiation of common lymphoid progenitor cells (CLP), defined as lineage-CD127 + CD117lowsca-1lowCD135+, into B lymphocytes in vitro, achieving an amplification factor of up to one hundredfold. We examined the roles of IL-7, Flt3L and SCF in differentiation of B cells from CLP in this culture system. Our findings indicate that IL-7 is a pivotal cytokine essential for B cell differentiation in vitro, demonstrating a notable synergistic impact when combined with SCF and FLT3L. Moreover, this system is capable of supporting the differentiation of hematopoietic stem cells (HSCs) and lymphoid-primed multipotent progenitor cells (LMPPs) into B cells in vitro. The findings substantiated the efficacy of the culture system in investigating the in vitro differentiation of bone marrow-derived progenitor cells into B cells and elucidated the specific roles of BSA, FBS and three cytokines (IL-7, FLT3L and SCF) in promoting efficient B lineage differentiation.